Հայոց Ցեղասպանության աշխարհաճանաչման խնդիրը Հովհ. Շիրազի «Հայոց դանթեականը» պոեմում - Խաչատրյան, Սիլվա (ԱրՊՀ հրատ․)
В статье "Проблема миропознания геноцида" в поэме Ов.Шираза "Айоц дантеакан" обсуждается и рассматривается цель и задача поэмы великого армянского поэта Ованеса Шираза, которая является осуждением Армянского геноцида 1915года. Поэма имеет мировое значение и является памятником о памяти полтора миллиона невинных армянских жертв геноцида 1915. In the article "The Problem of World Recognition of the Armenian Genocide" we discuss and consider the purpose and task of the great Armenian poet Hovhannes Shiraz "Hayots Danteakan" which is a condemnation of the Armenian Genocide of 1915. The poem has a global significance and is a tribute to the memory of one and a half million innocent victims of the Armenian genocide of 1915.
Keywords: Հայոց ցեղասպանություն; Արցախ